(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
Background: Deaths by ligation of neck are in practice from the time immemorial and before advent of civilization. In uncivilized societies, the application of ligation for taking away the life of another person was one of the commonest practices which were successfully carried out into the civilized societies. Hanging is that form of violent asphyxial death in which ligature marks are found and it is mainly based on the constricting forces which is : (i) either by the exclusion of air from lungs or oxygenated blood from the brain, (ii) by means of ligature around the neck, (iii) the constricting force is the weight of the body. Results: The data of present cross-sectional study of 100 cases with the aim, injuries over neck due to ligature was collected from in the Department of Forensic Medicine & Toxicology, Institute of Medical Science (IMS), BHU, Varanasi, U.P. India. The total duration of sampling was six months and different aspects such as sex ratio, age group involved, residence, ligature material used type of hanging, place of hanging, the Position of the knot and other external findings involved were taking under consideration. Conclusions: It was found that the most common cause of death in Varanasi region was Socio-economic Status of the victims with a male: female ratio of 1.8:1 with age group of 20- 29 years being most commonly involved.